1990
DOI: 10.1083/jcb.111.4.1673
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of plasminogen receptor expression on human monocytes and monocytoid cell lines.

Abstract: Abstract. The capacity of human monocytoid cell lines and peripheral blood monocytes to modulate their expression of plasminogen receptors has been assessed. After PMA stimulation, THP-1 or U937 monocytoid cells were separated into adherent and nonadherent populations. Plasminogen bound to adherent cells with similar capacity and affinity as to nonstimulated cells. In contrast, the nonadherent cells bound plasminogen with 5-17-fold higher capacity (without a change in affinity). This increase was selective as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
90
1

Year Published

1994
1994
2014
2014

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(99 citation statements)
references
References 65 publications
7
90
1
Order By: Relevance
“…The t-PA bound to the cells, and the binding was 78% inhibited by unlabeled t-PA, as well as by arginine and EACA, which also inhibits the binding of t-PA to other cell types (32).…”
Section: Figurementioning
confidence: 94%
See 1 more Smart Citation
“…The t-PA bound to the cells, and the binding was 78% inhibited by unlabeled t-PA, as well as by arginine and EACA, which also inhibits the binding of t-PA to other cell types (32).…”
Section: Figurementioning
confidence: 94%
“…Diisopropyl fluorophosphate (DFP) was used to inactivate t-PA, which was iodinated using the lactoperoxidase method, as described elsewhere (32).…”
Section: Methodsmentioning
confidence: 99%
“…By decreasing cellular plasminogen binding [78], CPN can reduce plasmin-dependent extracellular matrix degradation and cellular migration [77,81]. For example, freshly isolated monocytes, exposed to CPN in the plasma, bind about 30-fold less plasminogen than monocytes cultured for 18 h or longer [82]. As described above, plasmin can cleave both subunits of CPN, causing increased activity; proteolytically cleaved CPN is also more effective in reducing cellular plasminogen binding than native CPN [78].…”
Section: Hydrolysis Of Biologically Relevant Peptides In Vivomentioning
confidence: 99%
“…Both tPA and uPA have been shown to be expressed in a variety of cell types, including endothelial cells for tPA ( 51 ) and lung, kidney, and several tumor cell lines for uPA ( 52,53 ). It has been shown that tPA can directly bind to various cell types other than endothelial cells, such as platelets, monocytes, and monocytoid cells ( 30,39,54,55 ). Lp(a) was reported to inhibit plasminogen activation on the surface of resting platelets by inhibiting plasminogen and tPA binding ( 56 ).…”
Section: Role Of Carboxyl-terminal Lysines In Cell-dependent Plasminomentioning
confidence: 99%